Pasajeros en la tormenta. Variaciones sobre tres intelectuales italianos y el fascismo - Fernando J. Devoto (Centre de Recherches sur les Mondes Américains, 2020)
Left and right were at the core of intellectual debate in the so-called "age of extremes". Both were seen as antagonistic and irreducible. The article also suggests considering the numerous transits between the two poles, starting with the cases of three Italian intellectuals: Delio Cantimori, Ernesto de Martino and Cesare Pavese. Rather than proposing typologies or models, the research is oriented towards exposing the complexities of the individual paths that led many figures from fascism to communism. Without omitting to discuss the beliefs about the unity of the self and the rational or emotional alternatives in understanding these transits, the work highlights the need to address the various registers in which the activity of these figures is manifested and the various possible ways of linking continuities and ruptures in these movements. It concludes by stressing the importance of addressing both the data of individual displacement and the conditions of its social acceptability, firstly, in an intellectual community that used to demand additional justifications for such displacements. Finally, the paper reflects on the greater fluidity of displacement within the Italian intellectual space, which was crudely marked by the war, compared to the less traumatic Argentinean one.